Meningkatkan Kemampuan Sosial Anak Melalui Permainan Tradisional Congklak Pada Kelompok B Di Tk Negeri Pembina Kec.Woha Tahun Ajaran 2021 - Muazar Habibi; I Made Suwasa Astawa; Baik Nilawati Astini; Khofifah Desi Indarwati (Indonesian Publication Center, 2022)
There is a lack of social skills so that children are not able to interact well with their peers in Pembina Kec. Woha Kindergarten. Therefore the purpose of this study is to improve children's social skills through the traditional congklak game in group B at Pembina Kec. State Kindergarten. Woha Academic Year 2021. The type of research used is descriptive qualitative research. The research subjects were group B children, which consisted of 10 children. Data collection techniques in this study using observation techniques, interviews and documentation. Data analysis techniques in this study used descriptive analysis and statistical analysis. This research was conducted with several stages of observation including the first observation and the second observation. The results of the research on the 1st observation are that the child gets a score of 2 on several achievement indicators where the average value is 38.15% and this value is in the Starting to Develop (MB) category. Then an evaluation of the undeveloped indicators was carried out, including providing material reinforcement and giving enthusiasm and appreciation to the children then there was an increase in the second observation, the child got a score of 4 on several achievement indicators and the average score increased to 91.13% and the score in the Very Well Developed (BSB) category. Based on the results of this study, it can be concluded that playing congklak can improve the social skills of group B children in the Pembina State Kindergarten, Woha District.